A study of malicious software on the macOS operating system - Regensberg, Mark Alan (Rhodes University, Faculty of Science, Department of Computer Science, 2019)
Much of the published malware research begins with a common refrain: the cost, quantum and complexity of threats are increasing, and research and practice should prioritise efforts to automate and reduce times to detect and prevent malware, while improving the consistency of categories and taxonomies applied to modern malware. Existing work related to malware targeting Apple's macOS platform has not been spared this approach, although limited research has been conducted on the true nature of threats faced by users of the operating system. While macOS focused research available consistently notes an increase in macOS users, devices and ultimately in threats, an opportunity exists to understand the real nature of threats faced by macOS users and suggest potential avenues for future work. This research provides a view of the current state of macOS malware by analysing and exploring a dataset of malware detections on macOS endpoints captured over a period of eleven months by an anti-malware software vendor. The dataset is augmented with malware information provided by the widely used Virus. Total service, as well as the application of prior automated malware categorisation work, AVClass to categorise and SSDeep to cluster and report on observed data. With Windows and Android platforms frequently in the spotlight as targets for highly disruptive malware like botnets, ransomware and cryptominers, research and intuition seem to suggest the threat of malware on this increasingly popular platform should be growing and evolving accordingly. Findings suggests that the direction and nature of growth and evolution may not be entirely as clear as industry reports suggest. Adware and Potentially Unwanted Applications (PUAs) make up the vast majority of the detected threats, with remote access trojans (RATs), ransomware and cryptocurrency miners comprising a relatively small proportion of the detected malware. This provides a number of avenues for potential future work to compare and contrast with research on other platforms, as well as identification of key factors that may influence its growth in the future.
Keywords: Malware (Computer software); Computer security; Computer viruses; Mac OS